Predictors of challenging behaviour in adults with intellectual disability. Issue 6 (2nd November 2015) - Koritsas, Stella; Iacono, Teresa
Abstract : Purpose: – The purpose of this paper is to determine the extent to which mental health, physical health, communication, learned function of the behaviour(s), severity of disability, living arrangement, age, and gender, alone or in combination, predicted challenging behaviours in adults with intellectual disability. Design/methodology/approach: – In total, 74 adults with intellectual disability and their paid carers were recruited into the study from adult disability services in Victoria, Australia. Paid carers provided information about participants with intellectual disability on a range of measures targeting each variable of interest. Findings: – Based on principle components analyses of three challenging behaviour measures, two topographies of challenging behaviour emerged: contact and non-contact behaviours. Multiple regression analysis revealed that contact behaviours were predicted by anxiety scores and severity of disability. In addition to severity of disability and anxiety scores, non-contact behaviours were also predicted by sensory scores. Practical implications: – The results of the current study indicate that contact and non-contact behaviours were determined by multiple factors. Clinicians and others who work with people who display challenging behaviour may, therefore, find it helpful to utilise the biopsychosocial model in their formulations of possible reasons that motivate a person to engage in challenging behaviour. Originality/value: – These results contribute to the evidence base available to clinicians and researchers to guide future assessment for challenging behaviour. Expansion of functional assessment methods to explore factors not traditionally included, such as mental health and severity of intellectual disability, as causes of challenging behaviour, may prove helpful.